Consumer credit grievance and redress mechanisms: the Malaysia perspective - Ilias, Ibtisam @ Ilyana; Hassan, Rusni; Kassim, Salina; Abu Bakar, Elistina (Universiti Utara Malaysia Press, 2021)
This study examines the redress mechanisms accessible to aggrieved consumers dealing with various consumer credit providers in Malaysia. The existing legal and institutional framework characterised by the piecemeal approach has led different groups of consumers to varying levels of access, which can be superior or inferior to one another. The study employs a doctrinal legal research methodology in analysing the two alternative dispute resolution bodies, namely, the Ombudsman for Financial Services, and the Tribunal for Consumer Claims. Primary sources of law, namely, the Consumer Protection Act 1999, the Financial Services Act 2013, the Financial Services(Financial Ombudsman Scheme) Regulation 2014, the Hire-Purchase Act 1967, the Moneylenders Act 1951, and the Pawnbrokers Act 1972, are meticulously analysed along with secondary sources of law that principally comprise journal articles. The study reveals disparities in terms of access to cheap and simple redress mechanisms by various categories of consumers who are aggrieved by the actions of credit providers. The position of bank consumers and those entering into credit sale is accounted for, as there are particular ADR bodies established under relevant legislations to hear their respective disputes. On the contrary, the position of those who wish to lodge claims against moneylenders, pawnbrokers or credit companies offering hire-purchase is problematic. Several recommendations are proposed to resolve this opacity inter alia by referring to the approach adopted by South Africa. This study is significant in ensuring fair access to inexpensive and hassle-free dispute resolutions for all financial consumers, irrespective of the nature of their consumer credit transactions.